2011
DOI: 10.1111/j.1750-3841.2011.02056.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Antimicrobial Coating from Catfish Skin Gelatin on Quality and Shelf Life of Fresh White Shrimp (Penaeus vannamei)

Abstract: One of the most important technical and economic problems facing the shrimp industry is the relatively short shelf life of fresh shrimp products. Catfish skin gelatin-based antibacterial edible films/coatings provide an ideal technique to solve this problem. The shrimp industry will be the immediate beneficiary of the study, and the information provided by this research will be expended to other seafood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 40 publications
2
8
1
1
Order By: Relevance
“…e changes in pH of crayfish are shown in Figure 2(a). e initial pH value was 6.65, and it is similar to that of white shrimp [28]. e pH of CK and T0 samples significantly decreased (p < 0.05) at first and then increased from day 2 to the end.…”
Section: Ph and Electrical Conductivity Analysissupporting
confidence: 54%
“…e changes in pH of crayfish are shown in Figure 2(a). e initial pH value was 6.65, and it is similar to that of white shrimp [28]. e pH of CK and T0 samples significantly decreased (p < 0.05) at first and then increased from day 2 to the end.…”
Section: Ph and Electrical Conductivity Analysissupporting
confidence: 54%
“…This maybe because shrimp have a thick crust, which makes the penetration of marinated solution into the flesh difficult. Jiang had reported that most of the antibacterial ingredients were immobilized in the coating layer attached to the external shrimp shell, which made it much more difficult to interact with the shrimp flesh (Jiang and others 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Polyphenol treatment by reducing bacterial development as well as the related activity of endogenous enzymes slows down the rate of deterioration during storage. Antimicrobial coatings techniques are commonly applied to improve food safety, including seafood products (Dupard et al, 2006;Jiang et al, 2011;Guo et al, 2013). The polyphenolic extract used in present study seems to be potentially useful for this kind of applications.…”
Section: Bio-preservation Of Refrigerated Peeled Shrimp (Parapenaeus mentioning
confidence: 99%
“…A large variety of biochemical indicators may be used for characterization of shrimp quality and healthiness (Benner et al, 2003;Snellings et al, 2003). But as processing and in particular peeling may promote the development of a wide range of undesirable microorganisms including spoiling bacteria which lead to both health and economic concerns, microbiological indicators (Zeng et al, 2005, Dupard et al, 2006Jiang et al, 2011;Guo et al, 2013) are also considered essential. Generally, the total number of microorganisms, as total viable counts (TVC) has been used in mandatory seafood standards and in microbiological specifications of trading agreements.…”
Section: Introductionmentioning
confidence: 99%